The Effect of Financial Ratio Activities on the Value of a Company with Company Size as a Moderating Variable - Azizah, Yunita Isnani; Hidayat, Rendra Arief (Majapahit Journal of Islamic Finance and Management, 2025)
This research is motivated by the fluctuations in the performance of the food and beverage industry which contributes significantly to national economic growth, but the company value reflected in the Price to Book Value (PBV) is still unstable. The purpose of this study is to analyze the effect of financial ratios consisting of Return on Assets (ROA), Current Ratio (CR), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Sales Growth (SG) on company value, and to test the role of company size as a moderating variable. The study uses a quantitative approach and secondary data collected from 51 food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The analysis technique uses multiple linear regression and Moderated Regression Analysis (MRA). The results of the study show that partially, CR, TATO, and DER have a positive and significant effect on company value, while ROA and SG have a negative and significant effect. Simultaneous tests show that all independent variables have a significant effect on company value. Meanwhile, the results of the MRA analysis show that company size is able to moderate the influence of ROA, CR, TATO, and DER on company value significantly, but the nature of the moderation is to weaken the influence of the four ratios, and company size is unable to moderate the influence of SG on company value. This study concludes that management needs to strengthen financial performance through asset efficiency and profit growth, while investors can use certain financial ratios as investment considerations.